The Relationship Between Herd Size and Feed Cost in Beef Cattle Farming: A Case Study of H. Risnoto Farm, Tegal Regency, Indonesia - Muhammad Tubagus Fahmi; Ihsan Hilmi; Muhammad Evan Magistrama (Fakultas Peternakan. Unwiku, Purwokerto, 2026)
Feed is the single largest cost component in beef cattle enterprises, and understanding how it scales with herd size is essential for the economic sustainability of smallholder operations. This study examined the relationship between the number of cattle owned and the annual feed cost at H. Risnoto beef cattle farm in Tegal Regency, Central Java, Indonesia. A survey approach with a quantitative design was applied, using farm records covering the period 2020–2024. The number of beef cattle owned (head) and the corresponding total annual feed cost (Indonesian Rupiah, IDR) were collected and analysed using simple linear regression to determine the direction, strength, and statistical significance of the relationship. The analysis produced the regression equation Ŷ = 355,045,838 + 6,292,075X, with a coefficient of determination (R²) of 0.993 and a correlation coefficient (r) of 0.997 (p < 0.01). These results indicate a very strong, positive, and statistically significant association: each additional head increased the annual feed cost by approximately IDR 6.29 million. The strongly positive slope confirms that larger herds require proportionally greater quantities of forage and concentrate, raising total feed expenditure. However, the average feed cost per head rose only modestly across herd-size levels (from about IDR 3.95 million to IDR 4.57 million per head per year), suggesting limited economies of scale at the farm level. Farmers are advised to align herd size with their feed-supply capacity and to adopt efficient feeding strategies—such as the use of local feed ingredients and fermentation (silage) technology to keep the enterprise efficient and sustainable.